A rare case of a gastric adenomyoma mimicking a gastric duplication cyst - Esra Elif Arslan; Tuğba Acer Demir; Lütfi Hakan Güney; Merih Tepeoğlu; Müge Sağnak Akıllı; Akgün Hiçsönmez (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Arslan EE, Acer Demir T, Güney LH, Tepeoğlu M, Sağnak Akıllı M, Hiçsönmez A. A rare case of a gastric adenomyoma mimicking a gastric duplication cyst. Turk J Gastroenterol 2018; 29: 613-5.